West Coast Australia - Atkinson, Brett; Armstrong, Kate; Waters, Steve (Lonely Planet, 2015)
Lonely Planet West Coast Australia is your passport to themost relevant, up-to-date advice on what to see and skip,and what hidden discoveries await you. Swim beside whale sharks, snorkel among pristine coral, surf off seldom-visited reefs and dive at one of the world's premier locations at Ningaloo Marine Park, a World Heritage-listedmarine park; drift from winery to craft brewery along country roads shaded by tall gum trees at Margaret River, one of Australia's most beautiful wine regions; or discover the sophisticated restaurants showcasing modern Australian cuisine, chic cocktail bars hidden down unlikely lanes and the restored heritage buildings of Perth; all with your trusted travel companion. Get to the heart of the best of West Coast Australia and begin your journey now!